Evaluation of different pressed and extruded fish meal based diets on the growth of gilthead sea bream, Sparus aurata L. - Deguara S. (Feeding tomorrow's fish, 1997)
An experimental feeding trial was conducted concerning the effect of different sources of fish meal and feed manufacturing processes on the growth of Sparus aurata. The feeding trial was conducted within indoor experimental tanks for fourteen weeks using 60 g juvenile sea bream. The fish were fed four different fish meal based diets (Chilean, Danish, Danish Aqua and Danish Low Temperature). Each formulation was processed by two forms of pellet manufacture, steam pressing and extrusion. A control pressed standard commercial diet was also given. Fish fed the extruded feed were found to have performed better than the corresponding steam pressed feed in all nutritional parameters studied, whatever the type of fish meal used and in some cases significantly so. The best overall performance was found in the fish fed the extruded Danish fish meal based diet, followed closely by the extruded Danish Low Temperature fish meal based feed. In the case of the steam pressed feeds the Standard control feed, the Danish Aqua meal feed and the Danish Low Temperature meal feed gave the best performance for different nutritional parameters. The Chilean feed gave an inferior performance whatever the manufacturing method used. Protein sparing was observed in the fish fed the extruded feed compared with fish fed the corresponding steam pressed feed, and protein digestibilities were slightly higher in fish fed the extruded feeds. A higher carcass lipid content was also found in the fish fed the extruded feeds. The results of this study clearly show that extrusion had a positive effect on nutritional and growth performance compared to steam pressing, and that fish meal source and quality also had a profound effect on the nutritional value of the diet to sea bream.
Workshop of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1996/06/24-26, Mazarrón (Spain)